Congenital Human Cytomegalovirus Infection Inducing Sensorineural Hearing Loss - Xia, Wenwen; Yan, Hui; Zhang, Yiyuan; Wang, Congcong; Gao, Wei; Lv, Changning; Wang, Wentao; Liu, Zhijun (Frontiers in Microbiology, 2021)
Human cytomegalovirus is the primary cause of congenital infections. Despite its clinical significance, congenital HCMV infection is frequently overlooked clinically since most affected infants are asymptomatic. Sensorineural hearing loss is one of the most widely known disorders caused by congenital HCMV infection. The potential mechanism, however, remains unknown to date. The mechanism by which congenital HCMV infection induces sensorineural deafness has been partly characterized, leading to advancements in diagnosis, therapy, and prevention strategies. HCMV-induced hearing loss primarily involves immune responses, the release of inflammatory factors by NK cells, apoptosis of cochlear spiral ganglion, and potential changes due to vascular dysfunction. The diagnosis of HCMV induced sensorineural hearing loss includes serological examination to mothers, imaging, and amniotic fluid examination. Ganciclovir, mainly used for antiviral therapy and behavioral prevention, can, to some degree, prevent congenital HCMV infection. The role of HCMV infection in hearing loss needs further investigation since the mechanism of hearing loss caused by cytomegalovirus infection is not well understood. Although some advancement has been made in diagnosing and treating sensorineural hearing loss, more improvement is needed. A comprehensive understanding of cytomegalovirus's pathogenesis is of key importance for preventing, diagnosing, and treating sensorineural hearing loss.